Aquaporins and Their Regulation after Spinal Cord Injury - Andrea M. Halsey; Alex C. Conner; Roslyn M. Bill; Ann Logan; Zubair Ahmed (Cells, 2018)
After injury to the spinal cord, edema contributes to the underlying detrimental pathophysiological outcomes that lead to worsening of function. Several related membrane proteins called aquaporins (AQPs) regulate water movement in fluid transporting tissues including the spinal cord. Within the cord, AQP1, 4 and 9 contribute to spinal cord injury (SCI)-induced edema. AQP1, 4 and 9 are expressed in a variety of cells including astrocytes, neurons, ependymal cells, and endothelial cells. This review discusses some of the recent findings of the involvement of AQP in SCI and highlights the need for further study of these proteins to develop effective therapies to counteract the negative effects of SCI-induced edema.